PENGARUH MODEL PEMBELAJARAN CONNECTING, ORGANIZING, REFLECTING AND EXTENDING TERHADAP KOMUNIKASI MATEMATIS DAN DISPOSISI MATEMATIS SISWA KELAS VIII SMPN 4 PADANG PANJANG TAHUN PELAJARAN 2018/2019 - Sri Rukmala Putri (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematical Communication skills and mathematical disposition are two important aspects that need to be achieved in mathematics as the result of meaningful learning. In fact, learning activities in SMPN 4 Padang Panjang are not optimal in facilitating student to improve both aspects. Student have difficulties in presenting mathematical ideas in the form of images and statements into other forms of visual representation. One effort to resolve this problem by applying Connecting, Organizing, Reflecting and Extending (CORE) learning’s model in mathematics. This learning model helps students build their own knowledge. So, students will easy in communicate ideas that they have obtained. Besides, students constructing their own knowledge process. Students will have a high curiosity, self-confident and strong interest in studying mathematics, thus, math become students’ needs . This type of research is a Quasi-experimental design with non-equivalent post test, only control group design. The results of this study indicates that students’ mathematical communication who learn with CORE learning model is better than  conventional learning. Moreover, students’ mathematical disposition with CORE model is better than   conventional learning.Keywords - Mathematical Communication Skills, Mathematical Disposition, CORE Learning’s Model